2008
DOI: 10.1007/s11248-008-9215-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Sambucus nigra agglutinin (SNA-I′) from elderberry bark in transgenic tobacco plants results in enhanced resistance to different insect species

Abstract: Tobacco plants (Nicotiana tabacum cv Samsun NN) have been transformed with the gene encoding the type-2 ribosome-inactivating protein (RIP) SNA-I' from elderberry (Sambucus nigra) under the control of the Cauliflower Mosaic Virus 35S promoter. Previous research confirmed that these plants synthesize, correctly process and assemble a fully active RIP. Variability in protein expression was observed within the transgenic lines. The effects of the type-2 RIP SNA-I' delivered through a leaf feeding assay were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 38 publications
2
30
0
1
Order By: Relevance
“…Currently, the most widely available method to control aphid populations is the use of chemicals, but alternative methodologies such as plant genetic engineering offer new possibilities to enhance plant resistance to aphids. Among transgenes tested, lectins and proteinase inhibitors have been reported to promote deleterious effects on aphids (Gatehouse et al 2003;Rahbé et al 2003a,b;Dutta et al 2005;Shahidi-Noghabi et al 2009). In contrast, Bacillus thuringiensis d-endotoxins exhibit low to moderate toxicity in terms both of mortality and growth rate (Lawo et al 2009;Porcar et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most widely available method to control aphid populations is the use of chemicals, but alternative methodologies such as plant genetic engineering offer new possibilities to enhance plant resistance to aphids. Among transgenes tested, lectins and proteinase inhibitors have been reported to promote deleterious effects on aphids (Gatehouse et al 2003;Rahbé et al 2003a,b;Dutta et al 2005;Shahidi-Noghabi et al 2009). In contrast, Bacillus thuringiensis d-endotoxins exhibit low to moderate toxicity in terms both of mortality and growth rate (Lawo et al 2009;Porcar et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Lectins have been suggested as the cause of elderberry toxicity at least in insects (Michiels, Van Damme, & Smagghe, 2010). Amongst elderberry lectins we found one with ribosomeinactivating protein (RIP) activity known as nigrin, which coexists with a number of structurally-related monomeric and dimeric lectins devoid of RIP activity (Ferreras et al, 2010;Girbes et al, 2004;Stirpe, 2004) but with gut growth regulator activities (Pusztai et al, 1990) and toxicity to insect midgut (Michiels et al, 2010;Shahidi-Noghabi, Van Damme, & Smagghe, 2008;Shahidi-Noghabi, Van Damme, & Smagghe, 2009). Dwarf elder (S. ebulus L.) contains an equivalent of nigrin known as ebulin .…”
Section: Introductionmentioning
confidence: 99%
“…Shahidi-Noghabi et al (2009) reported that transgenic tobacco plants overexpressing SNA-I or SNA-I' enhanced the resistance to different insect species, including aphids and caterpillars. Mutation of the SNA-I B chain in one carbohydrate binding site reduced the insecticidal activity, while mutation of both carbohydrate binding sites completely abolished the toxic effect.…”
Section: Insecticidal Activity Of Ripsmentioning
confidence: 99%